2019
DOI: 10.1155/2019/5210730
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Thermo-Hydro-Mechanical-Chemical Modeling of Permeability Evolution in a CO2-Circulated Geothermal Reservoir

Abstract: The meager availability of water as a heat transfer fluid is sometimes an impediment to enhanced geothermal system (EGS) development in semi-arid regions. One potential solution is in substituting CO2 as the working fluid in EGS. However, complex thermo-hydro-mechanical-chemical (THMC) interactions may result when CO2 is injected into the geothermal reservoir. We present a novel numerical model to describe the spatial THMC interactions and to better understand the process interactions that control the evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 37 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…Important effects can happen due to chemical reactions, precipitation, dissolution, and swelling . This can be related to the high temperatures and large temperature differences manifest in geothermal applications, and the chemical response of different minerals and solutes present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Important effects can happen due to chemical reactions, precipitation, dissolution, and swelling . This can be related to the high temperatures and large temperature differences manifest in geothermal applications, and the chemical response of different minerals and solutes present.…”
Section: Discussionmentioning
confidence: 99%
“…Criticality develops in a similar fashion as the case above; the permeability is not more than completely reversed to the starting values-this is due to the elastic part of the response of the strain to the stresses [Colour figure can be viewed at wileyonlinelibrary.com] Important effects can happen due to chemical reactions, precipitation, dissolution, and swelling. 38,39 This can be related to the high temperatures and large temperature differences manifest in geothermal applications, and the chemical response of different minerals and solutes present. One can also think about the use of fluids different from water.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3. It can be observed that the maximum dry density ranged from 1.68 g/cm 3 to 1.83 g/cm 3 , where the corresponding optimum 3 Geofluids moisture contents are 21.2% to 17.4%, respectively. This phenomenon can be explained by the theory of electric double layer (EDL).…”
Section: Thermal Conductivity Testmentioning
confidence: 99%
“…According to the United Nations Educational, Scientific and Cultural Organization (UNESCO), over 1 billion hectares of saline soils or salt-affected soils are widely distributed in nearly 100 countries and regions, especially in arid and semiarid areas [1]; many of these areas are facing severe challenges of substantial air pollution and energy shortage caused by consuming fossil fuels for heating and cooling of the buildings [2]. Therefore, the renewable geothermal energy becomes a promising alternative to achieve thermal comfort due to its low cost, high availability, stability, and minimal environment impact and can be utilized by various geothermal subsurface earth structures such as geothermal energy piles (GEP), ground source heat pumps (GSHP), earth-air tunnel heat exchangers (EATHE), borehole thermal energy storage (BTES), geological carbon dioxide sequestration and storage, and geothermal heated pavement [3][4][5][6][7]. The basic principle of these projects is simple: a cold fluid (CO 2 or water) is injected into the buried pipe, absorbs heat from hotter surrounding soil, and then is pumped out [8].…”
Section: Introductionmentioning
confidence: 99%
“…To simplify the discussion, the swelling coefficient is assumed to be ω s S f ρ w f = 0:2. The strain resulting from dissolution can be expressed by considering the volumetric strain 40 as…”
Section: Simulation Proceduresmentioning
confidence: 99%